2016
DOI: 10.1016/j.triboint.2016.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Tribocorrosion of hard-on-hard total hip replacements with metal and ceramic counterfaces under standard and adverse loading conditions

Abstract: The hip simulator was fully instrumented with a three-electrode electrochemical cell to facilitate monitoring of corrosive degradation. The estimated volume loss from corrosion at the bearing surface was seen to increase by nearly an order of magnitude for both devices, representing as much as 17 % of total degradation. Anodic current transients also displayed near order of magnitude increases in the peak current for both bearing couples. An adverse loading scenario could cause as much as an order of magnitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…Polarization resistance ( R P ) values were derived from the LPR measurements, by calculating the slope of a linear fit to the linear portion of the E‐I curve, 22 in the Gamry EchemAnalyst software (Version 7.8.2, Gamry Instruments). Three valid independent measurements were used for these calculations ( N = 3) for 5 over 6 electrolytes ( N = 2 for BS + HA + 3 mM H 2 O 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…Polarization resistance ( R P ) values were derived from the LPR measurements, by calculating the slope of a linear fit to the linear portion of the E‐I curve, 22 in the Gamry EchemAnalyst software (Version 7.8.2, Gamry Instruments). Three valid independent measurements were used for these calculations ( N = 3) for 5 over 6 electrolytes ( N = 2 for BS + HA + 3 mM H 2 O 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…The applied metal alloys are mainly based on titanium, cobalt, iron, which has the distinguished passive corrosion behavior since an oxide film that develops at the surface spontaneously [3]. However, wear debris and release of metal ions due to the damage of oxide film have become the focus of much research due to extensive reported problems with some MoM devices [4].…”
Section: Introductionmentioning
confidence: 99%
“…This agreed with the steady-state values demonstrated both in Figure 6 and as reported previously. 28,29 Upon increasing the inclination to 40°the anodic currents immediately increased to 20-40 µA and again to 40-60 µA at 45°. At the final 50°inclination the anodic current increased to 60-70 µA for the first repeat and continued to climb to over 120 µA by the third repeat.…”
Section: Initiation Of Slidingmentioning
confidence: 97%